Is social coesion affecting heritage landscape preservation and interpretation? - Mascarenhas, José Manuel de (2013)
Summary: Usually heritage landscape is seen as a natural and a cultural resource. But, in the base of those landscapes we can meet social practices, an intangible heritage that give cohesion to the natural and cultural aspects. Our scope it's to debate ideas comparing examples. Between the well preserved Chinese rice heritage landscapes, suported by millenary social and farming practices, and the abandonned European terraces, an essential social question emerges: the preservation of the landscape heritage is supported not only by natural and cultural elements but also by social practices, technical knowlegde and ways of understanding Nature. Efforts to the heritage landscape maintenance has been limited to the natural and cultural elements preservation, forgotting often the referred social cohesion factors. To safeguard heritage, the cultural landscape should be duly interpreted which means the understanding of the ecological, social and even economic functionality of the landscape structures. Aim of the presentation: The main aim of the communication is to analyse how the preservation and interpretation of the landscape heritage depend not only on natural and cultural elements but also on the existence of traditional practices and social cohesion. This analysis is accompained with the comparision of existing terrace landscapes from Europe and others. The authors propose a landscape heritage monitoring method through the introduction of new indicators and the development of weighting coeficients strategies. Résumé of your experience in working with or studying interpretation: The authors are studying interpretation of cultural landscapes since the eighties (Project COST G2). They have developed heritage value criteria and monitoring indicators. Some works: Journal of Landscape Ecology, 4(1), 2011, pp.5-17; Journal of the Polish Association of Landscape Ecology, 30 (2011), 1-248; Landscapes: Perception, Knowledge, Awareness and Action, 1 (2012), pp.5-18